2010
DOI: 10.5483/bmbrep.2010.43.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Spry2 does not directly modulate Raf-1 kinase activity in v-Ha-ras-transformed NIH 3T3 fibroblasts

Abstract: Sprouty (Spry) proteins have previously been suggested as negative regulators of the MAPK pathway through interaction with Raf-1. However, the molecular basis of this inhibition has not been elucidated. In this study, we used cells expressing FLAGtagged Raf-1 with point mutations at known phosphorylation sites to reveal that activation of Raf-1 mutants does not correlate with their degree of interaction with Spry2. The association of Raf-1 with Spry2 in intact cells was further corroborated by immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Our recent data indicate that Spry2 may regulate Raf-1 kinase activity by acting as a scaffolding protein that brings Raf-1 kinase into close proximity with its direct regulators (Ahn et al, 2010). Here, we revealed that PDGF-induced Raf-1 activation was inversely correlated with the strength of interaction with Spry2 as monitored by co-immunoprecipitation experiment (Fig.…”
Section: The Change In the Interaction Between Raf-1 And Spry2 In Rasmentioning
confidence: 49%
See 2 more Smart Citations
“…Our recent data indicate that Spry2 may regulate Raf-1 kinase activity by acting as a scaffolding protein that brings Raf-1 kinase into close proximity with its direct regulators (Ahn et al, 2010). Here, we revealed that PDGF-induced Raf-1 activation was inversely correlated with the strength of interaction with Spry2 as monitored by co-immunoprecipitation experiment (Fig.…”
Section: The Change In the Interaction Between Raf-1 And Spry2 In Rasmentioning
confidence: 49%
“…In contrast to the detailed data collected on the Raf-1 activation process, the mechanism responsible for Raf-1 inactivation after signaling events is much less understood. Possible candidate for the feedback negative regulation of the Raf-1/MAP kinase pathway is the Sprouty (Spry) protein (Yusoff et al, 2002;Sasaki et al, 2003;Ahn et al, 2010), which was found to be a general inhibitor of receptor tyrosine kinases (Hacohen et al, 1998). Our study revealed that the expression level of Spry2 in Ras-NIH 3T3/Mdr cells was much higher than in their parental cells.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For immunofluorescence experiments, cells were grown on chamber slides (Nunc), and fixed in 10% formalin solution for 10 min as described (Ahn et al ., 2010). Samples were blocked with blocking solution (1% BSA, 0.6% Triton X-100 in PBS) for 1 h and incubated with primary antibodies diluted in blocking solution for 16 h at 4℃.…”
Section: Methodsmentioning
confidence: 99%
“…Anticancer activity is induced by promoting tubulin polymerization and inhibiting microtubules disassembly (2,3). Therefore, at subnanomolar concentrations, paclitaxel can block mitosis and inhibit cell proliferation (4). Since the Food and Drug Administration's approval of paclitaxel in 1982, it has also been approved to treat refractory ovarian cancer, metastatic breast cancer (5), AIDS-related Kaposi's sarcoma (6), and non-small cell lung cancer in many countries (7).…”
Section: Introductionmentioning
confidence: 99%